Percutaneous Deep Foot Vein Arterialization IVUS-Guided in No-Option Critical Limb Ischemia Diabetic Patients. (January 2021) - Cangiano, Gianluca; Corvino, Fabio; Giurazza, Francesco; De Feo, Eugenio Maria; Fico, Francesca; Palumbo, Vincenzo; Amodio, Francesco; Silvestre, Mattia; Corvino, Antonio; Niola, Raffaella
Purpose: To report our clinical experience with IVUS-guided percutaneous deep vein arterialization (pDVA) to treat chronic critical limb ischemia (cCLI) patients with no-endovascular or surgical options approach due to creation of an arteriovenous fistula (AVF). Materials and Methods: In a 2 years period, 14 no-option cCLI patients were treated with percutaneous deep vein arterialization (pDVA) by creating an AVF with a IVUS-guided system between posterior tibial artery and its satellite deep vein. Technical success was defined as successful AVF creation and venous perfusion of the wound site. Patients' characteristics, procedure details, mortality and wound outcomes were assessed prospectively. Results: Successful pDVA was successfully performed in all patients (mean age 82 years) without any procedural complications. Clinical improvement was achieved in all patients with resolution of rest pain, tissue formation of granulation tissue or both; only 3 major amputations were performed within the study period with a limb salvage rate of 78%. Median wound healing time was 4.8 months. Conclusion: pDVA is a safe and feasible revascularization technique alternative in no-option cCLI patients.